ASSESSMENT OF FINANCIAL AND ECONOMIC OBJECTIVES OF CREDIT RISK MANAGEMENT IN THE BANKING SYSTEM OF UKRAINE - OLIINYK, ANDRIY (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the current conditions of implementation and development of banking, bankers are paying more and more attention to the definition, assessment and measures to reduce the operational risk of the bank. Examples of this type of risk are personnel fraud, information system failures, and specific software failures that can result in significant losses and losses. In order to adequately protect against such risk, the bank must generate capital adequate to cover losses from the bank’s operational risk. The lack of systemic among the manifestations of the bank’s operational risk complicates the process of its identification, evaluation and management decisions. Therefore, the assessment of financial and economic prerequisites for operational risk management in the banking sector of Ukraine is becoming important in order to form an effective management system. The purpose of the article is to assess the financial and economic prerequisites for operational risk management in the banking system of Ukraine and determine their impact on the effectiveness of operational risk management of banking institutions. The main indicators of banks’ financial activity and functioning of payment systems in the banking system of Ukraine are analyzed. It is established that the level of operational risk increases with the increase in the volume of payment system transactions in banking. The assessment of financial preconditions of operational risk management in the banking system of Ukraine is carried out. The influence of financial and economic preconditions on the efficiency of operational risk management of banking institutions is determined and substantiated. Analysis of banks’ activity in the payment card market allows to identify negative aspects that necessitate improving the system of operational risk management of banks and finding ways to minimize them for the following reasons: increasing the share of non-cash payments by payment cards in trade and services compared to cash; expansion of the infrastructure for accepting payment cards; increase in revenues to local and state budgets due to fuller taxation of business entities and individuals (non-cash services sharply reduce opportunities for concealment of income.